An examination of in-season external training load in semi-professional soccer players: considerations of one and two match weekly microcycles - Swallow, W. E.; Skidmore, N.; Page, R. M.; Malone, J. J. (International Journal of Sports Science & Coaching, 2021)
The aim of the present study was to firstly, quantify the external training load (TL) of semi-professional soccer playersduring an annual season and secondly, to examine the influence of one (1MW) and two (2MW) match weekly micro-cycles. Data were collected from 24 semi-professional outfield soccer players during the 2018-2019 annual season usingmicro-electromechanical system (MEMS) devices for the following variables: Training duration (min), total distance (TD),Player Load (PL), high speed running (HSR) distance (5.5-7.0 m/s), and acceleration (ACC) efforts (>2m/s2). Trainingsessions were defined as days before match day (i.e. MD minus), with match weeks broken down as either 1MW or2MW. Data revealed higher TD, PL, and HSR distance on MD and MD-5 when compared to all other MD codes. MD-4displayed significantly higher values compared to MD-1 (mean differences (Mdiff): TD: 785 158 m; PL: 29 9 au; HSR:192 63 m; ACC: 15 3 #) and MD-2 (Mdiff: TD: 279 137 m; HSR: 127 54 m). During 2MW scenarios, bothTD (Mdiff: 685 328 m) and PL (Mdiff:33 14 au) were higher on MD-1 when compared to 1MW. However, lowervalues were observed for duration and HSR on MD-2 and MD-4 during 2MW compared to 1MW scenarios.These datasuggest that there appears to be a progressive reduction in TD, PL, HSR and ACC leading into competitive matchesbased on MD- analysis. However, some variability exists in TL prescription as a result of different MW scenarios (i.e.1MW vs. 2MW).